An extreme rotating black hole in New Massive Gravity Theory - Aceña, Andrés Esteban (2017)
New Massive Gravity is an alternative theory to General Relativity that is used to describe the gravitational field in a (2+1)-dimensional spacetime. Black hole solutions have been found in this theory, in particular an asymptotically anti-de Sitter rotating black hole. We analyse some features of this solution as its event horizon, black hole area and distance to the horizon, specially in the rotating extreme case, showing that they have shared features with extreme black holes in 4-dimensional General relativity. This limit case is interesting in the search of geometric inequalities as the ones found for the Kerr black hole in (3+1)-General Relativity.